Defining standards for fluoroscopy in gastrointestinal endoscopy using Delphi methodology - Khalaf, Kareem; Pawlak, Katarzyna M.; Adler, Douglas G.; Alkandari, Asma A.; Barkun, Alan N.; Baron, Todd H.; Bechara, Robert; Berzin, Tyler M.; Binda, Cecilia; Cai, Ming-Yan; Carrara, Silvia; Chen, Yen-I; de Moura, Eduardo Guimarães Hourneaux; Forbes, Nauzer; Fugazza, Alessandro; Hassan, Cesare; James, Paul D.; Kahaleh, Michel; Martin, Harry; Maselli, Roberta; May, Gary R.; Mosko, Jeffrey D.; Oyeleke, Ganiyat Kikelomo; Petersen, Bret T.; Repici, Alessandro; Saxena, Payal; Sethi, Amrita; Sharaiha, Reem Z.; Spadaccini, Marco; Tang, Raymond Shing-Yan; Teshima, Christopher W.; Villarroel, Mariano; van Hooft, Jeanin E.; Voermans, Rogier P.; von Renteln, Daniel; Walsh, Catharine M.; Aberin, Tricia; Banavage, Dawn; Chen, Jowell A.; Clancy, James; Drake, Heather; Im, Melanie; Low, Chooi Peng; Myszko, Alexandra; Navarro, Krista; Redman, Jessica; Reyes, Wayne; Weinstein, Faina; Gupta, Sunil; Mokhtar, Ahmed H.; Na, Caleb; Tham, Daniel; Fujiyoshi, Yusuke; He, Tony; Malipatil, Sharan B.; Gholami, Reza; Gimpaya, Nikko; Kundra, Arjun; Grover, Samir C.; Causada Calo, Natalia S. (Endoscopy International Open, 2024)
Background and study aims Use of fluoroscopy in gastrointestinal endoscopy is an essential aid in advanced endoscopic interventions. However, it also raises concerns about radiation exposure. This study aimed to develop consensus-based statements for safe and effective use of fluoroscopy in gastrointestinal endoscopy, prioritizing the safety and well-being of healthcare workers and patients.Methods A modified Delphi approach was employed to achieve consensus over three rounds of surveys. Proposed statements were generated in Round 1. In the second round, panelists rated potential statements on a 5-point scale, with consensus defined as ≥80% agreement. Statements were subsequently prioritized in Round 3, using a 1 (lowest priority) to 10 (highest priority) scale.Results Forty-six experts participated, consisting of 34 therapeutic endoscopists and 12 endoscopy nurses from six continents, with an overall 45.6% female representation (n = 21). Forty-three item statements were generated in the first round. Of these, 31 statements achieved consensus after the second round. These statements were categorized into General Considerations (n = 6), Education (n = 10), Pregnancy (n = 4), Family Planning (n = 2), Patient Safety (n = 4), and Staff Safety (n = 5). In the third round, accepted statements received mean priority scores ranging from 7.28 to 9.36, with 87.2% of statements rated as very high priority (mean score ≥ 9).Conclusions This study presents consensus-based statements for safe and effective use of fluoroscopy in gastrointestinal endoscopy, addressing the well-being of healthcare workers and patients. These consensus-based statements aim to mitigate risks associated with radiation exposure while maintaining benefits of fluoroscopy, ultimately promoting a culture of safety in healthcare settings.
Keywords: Pancreatobiliary (ERCP/PTCD); Cholangioscopy; Quality and logistical aspects; Delphi technique; Fluoroscopy; Radiation; Gastrointestinal endoscopy